Music in five, three and seven for saxophone quartet : 2010 - Van de Vate, Nancy 1930-2023 (American Composers Alliance, 2017)
Five, Three and Seven refer to the number of pitches found in the pitch sets which govern each of the six pieces
Cover title
Commissioned by the Styrian Saxophone Quartet and the Literary Society of St. Pölten, Austria, for the 2001 St. Pölten Summer Music Festival
Keywords: Woodwind quartets (Saxophones (4)) / Scores and parts; Chamber music; Scores; Parts (Music)